Block Copolymers Based on Ethylene and Methacrylates Using a Combination of Catalytic Chain Transfer Polymerisation (CCTP) and Radical Polymerisation. Issue 48 (22nd October 2021) - Baffie, Florian; Patias, Georgios; Shegiwal, Ataulla; Brunel, Fabrice; Monteil, Vincent; Verrieux, Ludmilla; Perrin, Lionel; Haddleton, David M.; D'Agosto, Franck
Abstract: Two scalable polymerisation methods are used in combination for the synthesis of ethylene and methacrylate block copolymers. ω‐Unsaturated methacrylic oligomers (MMAn ) produced by catalytic chain transfer (co)polymerisation (CCTP) of methyl methacrylate (MMA) and methacrylic acid (MAA) are used as reagents in the radical polymerisation of ethylene (E) in dimethyl carbonate solvent under relatively mild conditions (80 bar, 70 °C). Kinetic measurements and analyses of the produced copolymers by size exclusion chromatography (SEC) and a combination of nuclear magnetic resonance (NMR) techniques indicate that MMAn is involved in a degradative chain transfer process resulting in the formation of (MMA)n ‐b‐PE block copolymers. Molecular modelling performed by DFT supports the overall reactivity scheme and observed selectivities. The effect of MMAn molar mass and composition is also studied. The block copolymers were characterised by differential scanning calorimetry (DSC) and their bulk behaviour studied by SAXS/WAXS analysis. Abstract : Catalytic chain transfer polymerisation was used to produce methacrylic macromonomers. Those were involved in a simple radical polymerisation of ethylene to form block copolymers featuring a polyethylene segment and various polymethacrylic segments.